2023
DOI: 10.1097/md.0000000000033137
|View full text |Cite
|
Sign up to set email alerts
|

Associations between low birth weight and perinatal asphyxia: A hospital-based study

Abstract: To investigate the associations between low birth weight (LBW) and perinatal asphyxia by a hospital-based study. The participants of this study were mothers who gave birth at our hospital in 2018. They were divided into case group and control group according to their children’s asphyxia status. The bivariable and multivariable logistics regression were used to identify maternal and newborn factors with perinatal asphyxia. A total of 150 participants were enrolled in this study, including 50 participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
0
1
1
Order By: Relevance
“…In spite of the previous reports regarding the association between LBW and acidemia at delivery [40], we found that LBW was not associated with a change in neonatal cord pH during VE. We assume this association was not demonstrated due to the relatively small cohort, and further investigation is required in order to evaluate whether this association exists in the scenario of VE and suspected intrapartum distress.…”
Section: Discussioncontrasting
confidence: 99%
“…In spite of the previous reports regarding the association between LBW and acidemia at delivery [40], we found that LBW was not associated with a change in neonatal cord pH during VE. We assume this association was not demonstrated due to the relatively small cohort, and further investigation is required in order to evaluate whether this association exists in the scenario of VE and suspected intrapartum distress.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, our findings show that babies born with low birth weight has four times increased risk of birth asphyxia compared to normal weight babies. This finding is supported by multiple other studies including the ones done in Beijing Obstetrics and Gynecology Hospital and sub Saharan African, [ 31 , 32 ]. The pathophysiology for this is likely similar to that of preterm babies in which the respiratory systems are not fully developed [ 30 ].…”
Section: Discussionsupporting
confidence: 82%
“…Neste estudo não foi evidenciada influência significativa do sexo na existência de AN, no entanto alguns estudos demonstram que fetos masculinos são propensos a EHI (Chen et al, 2023;Li et al, 2023). A diferença de EHI entre homens e mulheres pode estar relacionada à diferença no nível de hormônio esteroide e no nível de função motora entre homens e mulheres (Chen et al, 2023).…”
Section: Discussionunclassified